SOCIALIZATION OF CENTRAL KALIMANTAN'S TYPICAL CULTURAL LEARNING DESIGN IN THE FRAMEWORK OF STRENGTHENING THE PROFILE OF PANCASILA AUD LEARNERS AMONG KINDERGARTEN TEACHERS IN GUGUS VIII BUNGA BOUGENVILLE PALANGKA RAYA - Sophia Oktavia Balimulia; Ignatia Imelda Fitriani; Cahaya Afriani Napitupulu; Esta Fronika Telaumbanua; Indria Saraswatie (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2023)
Understanding and implementing Pancasila is the obligation of all Indonesian citizens, therefore, love for the Indonesian homeland and a sense of pride in one's identity as an Indonesian child must be instilled from an early age. In the 2023/2024 academic year, the Ministry of Education and Culture has implemented the independent curriculum nationally, where the Pancasila Student Profile is the goal of National Education. Therefore, the activity of socializing learning designs typical of Central Kalimantan culture in order to strengthen the profile of Pancasila AUD students among teachers is considered important to carry out with the aim of increasing the potential of teachers in designing learning to strengthen the profile of Pancasila students based on the Independent Curriculum. Socialization of model designs and learning activities based on Central Kalimantan culture includes the introduction of Central Kalimantan batik, typical plants, Dayak language and others which aim to support Pancasila student profile projects implemented in PAUD institutions. This service activity is based on the Independent Learning Curriculum launched by the government through the Ministry of Education and Culture which includes I love the Earth, I Love Indonesia, the theme of playing and working together and My Imagination. These four themes aim to enrich insight and instill character from an early age, and in their implementation they are focused on topics chosen by the PAUD education unit according to the regional context and characteristics of students. The achievement of indicators of success in the socialization of Central Kalimantan Typical Cultural Learning Designs in the Context of Strengthening the Pancasila AUD Student Profile among Kindergarten Teachers in Cluster VIII Bunga Bougenville Palangkaraya, namely: a) Knowledge of Kindergarten Teachers in Cluster VIII Bunga Bougenville regarding learning designs Typical Central Kalimantan Culture in the context of strengthening profile of early childhood Pancasila students b) Kindergarten teachers' knowledge in implementing the steps to design learning for the Pancasila Profile Project which includes knowledge of strengthening the profile of Pancasila students, the process of preparing a school ecosystem, design forms for projects strengthening the profile of Pancasila, knowledge of managing projects strengthening the profile of Pancasila, knowledge of documentation and reporting the results of the project to strengthen the Pancasila profile as well as understanding the evaluation and follow-up to the project to strengthen the Pancasila profile. The output produced from this PKM is in the form of 1) Videos and photos of activities; 2) Publication on online social media (Instagram); 3) Publication in SINTA 5 journals; 4) HAKI.